Kadar Protein Kecap Kara Benguk Dengan Variasi Volume Ekstrak Nanas Dan Waktu Hidrolisis Enzimatis - Fisandriya, Heldha Ayu; , Dra. Aminah Asngad, M.Si (2015)
Velvet bean is native to Indonesia classified in Leguminoseae. Protein content is almost the same that can be processed ketchup. This experiment uses enzyme bromelain from pineapple fruit extracts. The enzyme bromelain works to break down the protein can speed up the manufacture of ketchup. The purpose of experiment to determine the protein levels velvet bean ketchup and quality organoleptic with velvet bean ketchup the addition of pineapple extract volume and hydrolysis time enzymatic. The method used in this research completely randomized design (CRD) two factors. These factors are pineapple extract volume (V) (100 ml, 120 ml, and 140 ml) and hydrolysis time enzymatic (W) (1 day, 3 days, and 5 days). The results showed that addition of pineapple extract influenced the protein content of ketchup. This experiment used 9 treatment that V1W1, V2W1, V3W1, V2W1, V2W2, V2W3, V3W1, V3W2, and V3W3 with test results protein content of 1.689%; 1.948%; 1.668%; 2.165%; 2.113%; 1.971%; 1.640%; 1.841%; and 1.685%. The highest protein content in V2W1 treatment of 2,165% while the lowest protein content on V3W1 treatment of 1.640%. Ketchup with pineapple extract treatment volume of 100 ml and 1 day hydrolysis time is ketchup that can be accepted by society.